Resistance to crack propagation of green composites - Ch'ng, Zi Wei (2011)
This project investigates the crack growth stability in a natural fibre reinforced epoxy polymer composite. KFRP composite panels were fabricated from Kenaf fibre and an epoxy matrix system via two different manufacturing routes, i.e. Vacuum Casting (VC) method and Resin Transfer Moulding (RTM) method. For VC, the composite panels were casted on a mould at room temperature for 24 hours, followed by 80 oC post cured for 16 hours. For RTM, the injection was conducted at room temperature with 276 kPa (40 Psi) pressure and cured at 80 oC for 16 hours. The fibres of some composite panels were dried before the manufacturing process, and some were treated with plasma or bioenzyme. The effect of manufacturing methods and fibre treatment to crack growth stability and Mode I Interlaminar Fracture Toughness of KFRP composites were evaluated. Crack growth was stable in RTM manufactured KFRP at loading rate of 5 mm/min. However, a reduced loading rate of 0.5 mm/min was required for VC manufactured KFRP just to show limited and unstable crack growth. The interlaminar fracture toughness of RTM manufactured composite was evaluated to be 1020 J/m2. Plasma treatment and bioenzyme treatment were able to increase the fracture toughness to 1196 J/m2 and 1114 J/m2 respectively. Nevertheless, these treatments had caused the crack growth pattern to be relatively unpredictable compared to untreated KFRP composites.